Underwater Sensor Networks for Communication, Navigation, and Localization - Ullah, Inam (Sensors (Basel, Switzerland), 2025)
Around 70% of the Earth is covered by water, with numerous submerged locations that have yet to be monitored and supervised [...].Around 70% of the Earth is covered by water, with numerous submerged locations that have yet to be monitored and supervised [...].